2001
DOI: 10.1590/s0100-204x2001001200002
|View full text |Cite
|
Sign up to set email alerts
|

Graus de resistência à brusone e produtividade de cultivares melhoradas de arroz de terras altas

Abstract: O objetivo deste trabalho foi estudar o nível de resistência à brusone nas folhas e panículas e seu efeito sobre a produtividade de 12 cultivares de arroz, em experimento de campo, durante três anos consecutivos. O grau de resistência das cultivares à brusone nas folhas e panículas foi determinado utilizando-se o critério de área sob curva de progresso e severidade de brusone nas panículas dez dias antes de colheita, respectivamente. As cultivares Progresso, Cuiabana, Caiapó, Carajás e Araguaia, em ordem decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Of course, this behaviour is completely expected as the breeding programmes select for a multitude of traits, mainly related to productivity and not solely for disease resistance. The high gains for specific selection based only in disease would very likely not be translated in gains in other important traits as grain yield, since correlations between resistance to disease and yield, although positive, are not particularly high (Prabhu & Filippi, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this behaviour is completely expected as the breeding programmes select for a multitude of traits, mainly related to productivity and not solely for disease resistance. The high gains for specific selection based only in disease would very likely not be translated in gains in other important traits as grain yield, since correlations between resistance to disease and yield, although positive, are not particularly high (Prabhu & Filippi, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Improved rice cultivars, such as IAC 202 and Caiapó, are superior in grain quality to Rio Paranaíba and Araguaia but susceptible to blast (Prabhu & Filippi, 2001). There has been considerable emphasis on the integrated rice blast control including fungicides as one of the inputs to keep the disease at tolerable levels (Filippi & Prabhu, 1997a).…”
mentioning
confidence: 99%
“…Rodríguez et al (1998) showed high leaf blast variability in rice genotypes and concluded that the resistance level of some genotypes is low and requires complementary control measures. Prabhu and Filippi (2001) demonstrate the relevance of incorporating resistance genes in new genotypes against the most frequent breeds of the pathogen.…”
Section: A B C Dmentioning
confidence: 95%